Analisis Kebutuhan Air Bersih PDAM Tirta Kualo di Kecamatan Datuk - Z, Fynnisa; Irwansyah, Muhammad; Hasanah, Moraida; Siregar, Zuraidah; P, Sophia Az Zahra; Aprilia, Risma (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2024)
Water is one of the most vital sources of livelihood for all living things on earth. However, not all people have the ability to process water. Datuk Bandar District is one of the areas that has a large number of residents and facilities for schools, offices and other public facilities. In this study, we analyze the demand for domestic and non-domestic clean water in Datuk Bandar District for the next 20 years by projecting the need for population growth until 2041 based on data from the Central Statistics Agency. The method used in this study is the method of arithmetic, geometry, and least square. From the results of the analysis, the projected population of Datuk Bandar Subdistrict in 2041 using the geometric method is 81,670 people and the projected clean water needs of 85,105 l/second, while for now the production capacity of PDAM Tirta Kualo for Datuk Bandar Subdistrict is in WTP II service, namely of 90 l/sec. so that until 2041 the need for clean water for Datuk Bandar District is still fulfilled.